Wan phatthanā - Bhumibol Adulyadej, King of Thailand, 1927- (Krom Kanphatthana chumchon, Krasūang Mahātthai, 1996)
On community and rural development in Thailand specially refered to the role of Bhumibol Adulyadej, King of Thailand, b. 1927, commemorative volume brought out at development day and 50th anniversary of his coronation day.